a) \(...=\left(x-\sqrt{11}\right)\left(x+\sqrt{11}\right)\)
b) \(...=\left(x-\sqrt{22}\right)\left(x+\sqrt{22}\right)\)
c) \(...=\left(x+\sqrt{7}\right)^2\)
d) \(...=\left(x-\sqrt{23}\right)^2\)
e) \(...=\sqrt{x}\left(\sqrt{x}+1\right)\)
f) \(...=\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)\)
g) \(...=\left(\sqrt{x}-\sqrt{y}\right)\left(\sqrt{x}+\sqrt[]{y}\right)\)
h) \(...=\left(\sqrt{x}+1\right)^2\)
i) \(...=\sqrt{x}\left(x+1\right)-\left(x+1\right)=\left(\sqrt{x}-1\right)\left(x+1\right)\)
k) \(...=x+10\sqrt{x}-\sqrt{x}-10=\sqrt{x}\left(\sqrt{x}+10\right)-\left(\sqrt{x}+10\right)=\left(\sqrt{x}-1\right)\left(\sqrt{x}+10\right)\)